Molecular mechanisms of axon guidance. - Chilton, J.K. (Developmental Biology, 2006)
In order to form a functional nervous system, neurones extend axons, often over long distances, to reach their targets. This process is controlled by extracellular receptors and their ligands, several families of which have been identified. These proteins may act to either repel or attract growth cones and a given receptor may transduce either type of signal, depending on the cellular context. In addition to these archetypal axon guidance molecules, it is becoming apparent that molecules previously known for their role in patterning can also direct axonal outgrowth. The growth cone receptors do not act in isolation and combine with members of the same or other families to produce a graded response or even a complete reversal in its polarity. These signals can be further combined and/or modulated by processing of the molecule both directly at the cell surface and by the network of intracellular signalling pathways which are activated. The result is a sophisticated and dynamic set of cues that enable a growth cone to successfully navigate to its destination, modulating its response to changing environmental cues along its pathway.